2018
DOI: 10.1111/bcpt.13039
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Hepatic Retinaldehyde Dehydrogenase Induction to Impairment of Glucose Metabolism by High‐Fat‐Diet Feeding in C57BL/6J Mice

Abstract: Obesity and insulin resistance are associated with overexpression of retinaldehyde dehydrogenase 1 (RALDH1). We aimed to investigate the roles of hepatic RALDH1 induction in glucose metabolism impairment using mice fed with high-fat-diet (HFD). Mice were fed with HFD for 8 weeks and treated with RALDH inhibitor citral for another 4 weeks. Oral glucose tolerance test (OGTT), pyruvate tolerance test (PTT) and insulin tolerance test were performed. Expressions of phosphoenolpyruvate carboxykinase 1 (PCK1), glucok… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…Immune system includes detect pathogen, phagocytic activity, cytotoxicity, encapsulation, wound healing, and proPO activation (Xu et al, 2018). The result of this study showed that THC in shrimp reared with the addition of citral treatment in feed was higher than control.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…Immune system includes detect pathogen, phagocytic activity, cytotoxicity, encapsulation, wound healing, and proPO activation (Xu et al, 2018). The result of this study showed that THC in shrimp reared with the addition of citral treatment in feed was higher than control.…”
Section: Discussionmentioning
confidence: 74%
“…This is thought to be caused by two things, the first is an inhibition in glucose absorption process from intestine into the blood or the second is an increase in the rate of blood glucose absorption into the liver tissue or other organ. The previous study in rat showed that citral could decrease blood glucose level and increase insulin plasma concentration in diabetic rat (Mishra et al, 2019;Xu et al, 2018). Xu et al, 2018 showed that therapeutic effect of citral in glucose metabolism associated with the increase of insulin sensitivity and the decrease of endogenous glucose production in diabetic rat, furthermorem citral concentration influenced these effects.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The natural product citral has been known for many years to be an aldehyde dehydrogenase inhibitor, and it has routinely been used to block ATRA synthesis in the laboratory ( Xu et al, 2018 ; Kikonyogo et al, 1999 ).…”
Section: Resultsmentioning
confidence: 99%
“…The levels then stabilize and return to normal within 8 weeks after treatment is stopped. Therapy should be stopped if the triglyceride level exceeds 8.0 mmol/l because of a risk of pancreatitis [16]. More dramatic increases in the triglyceride level have been observed in patients who were obese, consumed excessive amounts of alcohol, had a family history of hyperlipidaemia or other risk factors [17].…”
Section: Discussionmentioning
confidence: 99%